1984
DOI: 10.1017/s0043174500059804
|View full text |Cite
|
Sign up to set email alerts
|

Penetration, Translocation, and Metabolism of Acifluorfen Following Pretreatment with Mefluidide

Abstract: The penetration, translocation, and metabolism of acifluorfen {5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitrobenzoic acid} in ivyleaf morningglory [Ipomoea hederacea(L.) Jacq. ♯3IPOHE], velvetleaf (Abutilon theophrastiMedic. ♯ ABUTH), common cocklebur (Xanthium pensylvanicumWallr. ♯ XANPE), and soybean [Glycine max(L.) Merr.] were studied. An application to plants of 0.3 kg ai/ha mefluidide {N-[2,4-dimethyl-5-[[(trifluoromethyl)sulfonyl] amino] phenyl] acetamide} 0, 3, 5, or 7 days prior to treatment with14C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Translocation in barley (Hordeum vulgare L.) and wheat was greater at 6 h after treatment (15 and 10%), respectively, but decreased over time (24 to 96 h), staying at 3.9% in barley and ranging from 4.1 to 8.5% in wheat. Translocation in Italian ryegrass increased over time to 9.4% at 96 h. Hook and Glenn (1984) observed that translocation of 14 C-acifluorfen in common cocklebur increased, with 1.3 or 1.6% of the amount applied found above or below the treated leaf, respectively, with acifluorfen alone and 4.6 or 4.3%, respectively, when mefluidide was applied 7 d earlier.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Translocation in barley (Hordeum vulgare L.) and wheat was greater at 6 h after treatment (15 and 10%), respectively, but decreased over time (24 to 96 h), staying at 3.9% in barley and ranging from 4.1 to 8.5% in wheat. Translocation in Italian ryegrass increased over time to 9.4% at 96 h. Hook and Glenn (1984) observed that translocation of 14 C-acifluorfen in common cocklebur increased, with 1.3 or 1.6% of the amount applied found above or below the treated leaf, respectively, with acifluorfen alone and 4.6 or 4.3%, respectively, when mefluidide was applied 7 d earlier.…”
Section: Resultsmentioning
confidence: 85%
“…Other studies have documented changes in herbicide absorption as a result of earlier herbicide applications. Hook and Glenn (1984) observed an increase in absorption (36, 57, and 50%) of acifluorfen when common cocklebur (Xanthium pensylvanicum Wallr.) received a mefluidide application 3, 5, or 7 d before 14 C-acifluorfen application, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…In some instances the model predicted more than 3 times the amount of xenobiotic absorbed in comparison to the actual absorption. The model predictions of absorption were overestimated for herbicides such as acifluorfen (135), imazaquin (145), imazethapyr (147), nicosulfuron (150), prosulfuron (152),sethoxydim (153) and Halosulfuron (154). These overestimations of xenobiotic absorption represent only 14% of the simulations ( Table 3).…”
Section: Comparison Between Model Prediction Of Xenobiotic Uptake Andmentioning
confidence: 99%
“…), na Europa (a tradição marxiana etc. ), no Japão (Hook;Kan, 1983) e noutros lugares começaram a identificar-se como sendo investigação para a paz e a marcar presença em associações, revistas e congressos. Esta natureza dupla do processo de crescimento teve consequências importantes.…”
Section: Håkan Wibergunclassified